Handmade Double-Sided Toggle Pin Technique for Repairing Coxofemoral Luxation in a Dysplastic Golden Retriever - Jekinakatti, Kanteshkumar Mahadev; Jekinakatti, Sannathkumar Mahadev; N, Umapati (Medical Science: Trends and Innovations Vol. 11, 2025)
A two-year Male, 27.5 kg Golden Retriever was presented to the Department of Veterinary Surgery and Radiology at Veterinary College Hassan after being caught in a neck chain, resulting in limping in the left hindlimb. On physical examination, shortening of the left hindlimb along with swelling and pain on palpation of the left hip joint, was observed. Orthopaedic and radiographic exams confirmed cranio-dorsal coxofemoral luxation in the left hindlimb, accompanied by bilateral hip dysplasia. Under general anaesthesia, the coxofemoral luxation was corrected via a cranio-dorsal approach using handmade toggle pins (1.5 mm K-wire) and nylon thread (1 mm diameter). Post-operative radiographs confirmed proper alignment and anatomical configuration of the coxofemoral joint with toggle pins securely in position. Post-operatively, a pelvic bandage and Robert Jones bandage were applied to the operated left hindlimb. The dog was treated with Cefpodoxime proxetil (10 mg/kg), Tramadol (2 mg/kg) and Deep TBR tablets for five days, along with FlexiRun tablets and restricted activity with short leash walks. The dog began using the affected limb on the second post-operative day, showing slight lameness initially, but was walking without lameness by the 45th post-operative day. The animal recovered uneventfully with good weight-bearing capability. In conclusion, the double-sided modified toggle pin technique using handmade toggle pins proved to be an economical and practical method for repairing coxofemoral luxation, offering good clinical outcomes with rapid recovery.